QUALIFICATIONS FOR COLLEGE ACCOUNTING TEACHERS. - Price, Harry R. (The Accounting Review, 1957)
Before discussing the problem of what constitutes desirable qualifications for college accounting teachers, the general aims and objectives of the four-year college program should be considered, based upon the opinions of leaders, both in the field of education and of business. The objectives of college accounting programs have been widely discussed. The variety of opinions ranges from the feeling that accounting is purely vocational in nature to the conviction that accounting is a liberal arts subject. The American Institute of Accountants devoted a considerable portion of their 1948 convention to studying the training problems of public accountants. Their findings were published in "New Responsibilities of the Accounting Profession." In a recent survey completed by the writer upon "Accounting Education at the University Level" questions were included for the purpose of obtaining the opinions of college accounting professors, certified public accountants, and industrial accountants, regarding the general and vocational objectives of college accounting courses, along with the suggested qualifications for college accounting teachers of these subjects.